2019
DOI: 10.1186/s13256-019-2084-x
|View full text |Cite
|
Sign up to set email alerts
|

Acute odontogenic infection combined with crowned dens syndrome: a case report

Abstract: Background Calcium pyrophosphate dihydrate crystal deposition disease is a condition in which calcium pyrophosphate dihydrate crystal is deposited in joint cartilage and ligaments. Calcium pyrophosphate dihydrate crystal deposition disease that involves calcification around the odontoid process of the second cervical vertebra is called crowned dens syndrome. Crowned dens syndrome is accompanied by fever in addition to acute and intense neck, posterior head, and temporal pain; thus, distinguishing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…In our study, 10 cases of CDS occurred during hospitalization, two of which took more than 2 days to be diagnosed. Previous studies have also reported multiple cases of CDS during hospitalization for dental infection, 9 post brain surgery, 16 post endoscopic retrograde cholangiopancreatography, 22 pneumonia, 23 and after acute cerebral infarction 24 . New symptoms such as fever during hospitalization may be due to flare‐ups of the primary disease, side effects of medication, or complications of invasive procedures such as catheterization, making CDS diagnosis even more difficult than in outpatients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In our study, 10 cases of CDS occurred during hospitalization, two of which took more than 2 days to be diagnosed. Previous studies have also reported multiple cases of CDS during hospitalization for dental infection, 9 post brain surgery, 16 post endoscopic retrograde cholangiopancreatography, 22 pneumonia, 23 and after acute cerebral infarction 24 . New symptoms such as fever during hospitalization may be due to flare‐ups of the primary disease, side effects of medication, or complications of invasive procedures such as catheterization, making CDS diagnosis even more difficult than in outpatients.…”
Section: Discussionmentioning
confidence: 99%
“…It is of interest that, although the majority of CDS cases were treated with NSAIDs, acetaminophen was prescribed in as many as 1/4 of cases. Two previous CDS reports from Japan also used acetaminophen for treatment 9,20 . Acetaminophen has become the first‐line drug of choice in the management of mild chronic pain in the elderly due to its safety profile compared to NSAIDs 29 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to the gout frequently occurring in older adult males, pseudogout is more common in older adult females. Pseudogout frequently affects the knees, hands, shoulder joints, elbow joints and feet, and it occasionally occurs in the cervical, thoracic and lumbar spine (55). Pseudogout occurring around the cervical odontoid process may cause neck pain, which usually manifests as acute or subacute moderate to severe neck pain, even restricted cervical range of motion and occipital pain (25).…”
Section: Discussionmentioning
confidence: 99%